Violence and the Sacred, 2021 - Gans, Eric Lawrence (2021)
My objections to René Girard’s scapegoat model of the originary human scene should not be taken to imply that the sacred and human violence are not intimately related. But violence is sacred only in the sense that the sacred is taboo; the primary, although unfortunately not the sole, cultural function of the discharge of violence...